Gambling products and their risk potential for gambling disorder - Mravčík, Viktor; Chomynová, Pavla; Grohmannová, Kateřina; Rous, Zdeněk (Casopis lekaru ceskych, 2020)
Gambling brings excitement, which is a part of entertainment, but also a basis of operant conditioning, which, in conjunction with other biological and psychological factors, leads to the loss of control over the player's behaviour. This gambling disorder (problem gambling) is characterized by a high intensity and episodic character of gambling and a high amount of staked money, with negative consequences to players and their close ones. Problem gamblers have a high rate of psychiatric comorbidity, as well as suicide. Various gambling products pose a different risk of problem gambling. The game's risk is determined by the arousal for players, the social nature of the game, or the degree of skill required for gambling. It is an effect of so-called structural and situational characteristics, such as amount and variability of bets, structure and probability of win, jackpot, game speed, near wins, audio and visual effects, etc. The game risk increases also with its accessibility or with substance use while playing. In the Czech Republic, there is a high availability of electronic gaming machines (EGM) compared to the neighbouring countries; the availability of on-line games has increased dramatically in recent years. There is also an observed increase in participation in on-line gambling, not just odds and live betting, but also technical games or casino games as reported in population surveys. Estimated up to 5.7% of the adult population is at risk of problem gambling (approx. 510 thousand persons), of which 1.2-1.4% are at a high risk (approx. 80-120 thousand persons). EGMs represent the highest risk, but also casino or on-line games including odds betting, especially live betting shows high risk of problem gambling. Most of the problem gamblers are men; especially young men are highly vulnerable. Although the new Gambling Act has introduced a number of new preventive measures since 2017 according to basic types of games, the assessment of the risk potential of particular gambling products is not a part of their licensing. This contributes to increasing availability of high-risk games, especially on-line.
Keywords: structural characteristics; Česká republika; situational characteristics; Czech Republic; Adult; Male; lidé; dospělí; hráčství; mužské pohlaví; gambling disorder; Humans; gambling; Gambling